การพัฒนารูปแบบการเรียนการสอนแบบผสมผสาน ด้วยการเรียนแบบทักษะปฏิบัติร่วมกับเครื่องมือทางปัญญาผ่านคลาวด์คอมพิวติ้ง เพื่อเสริมสร้างทักษะความคิดสร้างสรรค์ และการสร้างผลงานศิลปะของนักเรียนมัธยมศึกษาตอนปลาย - เฉลิมสุข ณัฐวรรณ; สติมั่น อนิรุทธิ์ (Journal of Education Studies, Chulalongkorn University, 2019)
This study aims to develop integrated teaching and learning pattern with practice skill learning and cloud computing intelligent tool to enhance creative skill and create art work of high school students. The samples in this study were 113 high school students of the demonstration school selected with the method of simple random sampling. The research tools were consisted of 1) questionnaires of problem conditions and needs, 2) the pattern of teaching and learning integrated pattern with practice skill learning and cloud computing intelligent tool, 3) learning management plan and 4) the appropriateness evaluation of the teaching and learning. The results found that, ﬁrstly, the developed pattern was composed of six elements; 1) learning activities 2) learning sources 3) feedbacks 4) communication between learners and teachers 5) communication between learners and learners and 6) learning outcome evaluation. Moreover, the integrated teaching and learning activities contained six steps; 1) ﬁnding and creation the inspiration (perception), 2) data gathering (perception), 3) idea motivation (perceptive response), 4) thoughtfully examining (practice and skillful performance), 5) communication between learners and learners and 6) learning outcome evaluation. The integrated teaching and learning activities contained six steps; 1) ﬁnding and creating inspiration (perception), 2) data gathering (perception), 3) idea motivation (perceptive response), 4) thoroughly examining (practice and skillful performance), 5) initiating identity (adaptation) and 6) criticizing and evaluating. Secondly, the result of the integrated teaching and learning pattern assessed by the experts found that the appropriateness was high (4.47, SD = 0.02). Thirdly, for the evaluation of the integrated instruction Model assessed by the experts, the appropriateness was in the good level.